Hintonelmis spila sp. nov. (Elmidae: Elminae): a new species of riffle beetle from Amazonian region - Pinedo-Garcia, Raul Bismarck; Hamada, Neusa; Nascimento, Jeane Marcelle Cavalcante Do (Zootaxa, 2024)
A new species, Hintonelmis spila sp. nov. from Brazil, Guyana, and Suriname, is described, illustrated, and diagnosed. The new species can be distinguished from all known species of the genus by the coloration pattern of the elytra (a pair of elongated yellowish-brown patches near the humeral region, a second pair is shorter than the first one, and situated approximately on apical 3/5, and an apical patch along the elytral suture). The combination of characters of the male genitalia can be helpful to distinguish species: the parameres are 3/5 the length of the penis, the phallobase is shorter than the penis, and it is three times longer than wide, and the penis is 6.2 times longer than wide.